Promoting Sustainable Financial Services through Cashless Transactions: An Empirical Analysis of Small and Medium Enterprises (SMEs) in Nepal - Chaudhary, Manoj Kumar; Adhikari, Madhav; Ghimire, Dinesh Mani; Dhungana, Madan (Devkota Journal of Interdisciplinary Studies, 2024)
Digital financial technologies are reshaping the economic landscape, enhancing financial inclusion and sustainable development. This study examines the adoption of cashless transactions among Small and Medium Enterprises (SMEs) in Nepal, focusing on factors like privacy, security, and resource availability through the Technology Acceptance Model (TAM). A structured survey was utilized to gather information from 389 SME owners in the Kathmandu Valley as part of a cross-sectional study design. Path analysis and other quantitative techniques were used to investigate the connections between the adoption of cashless transactions and the main adoption drivers, which include perceived usefulness, perceived ease of use, social influence, privacy concerns, and resource availability. Results show a strong link between these factors and adopting electronic payment systems, with privacy and security being the most significant. While perceived ease of use and usefulness drive adoption, challenges like limited digital literacy and infrastructural constraints exist, especially in rural areas. This study highlights how cashless transactions can help SMEs become more resilient and operationally efficient, which aligns with global trends. It offers practical advice on how financial service providers and legislators can remove obstacles, encourage digital inclusion, and build a strong digital ecosystem.